A 3D polyacrylonitrile nanofiber and flexible polydimethylsiloxane macromolecule combined all-solid-state composite electrolyte for efficient lithium metal batteries. Issue 26 (1st July 2020) - Gao, Lu; Li, Jianxin; Sarmad, Bushra; Cheng, Bowen; Kang, Weimin; Deng, Nanping
Abstract : A composite polymer electrolyte is synthesized, which has an improved ionic conductivity, superior interface compatibility and sufficient dendrite inhibition ability, bringing excellent electrochemical performance to all-solid-state batteries. Abstract : All-solid-state polymer electrolytes have received widespread attention due to their superior safety over liquid electrolytes that are prone to leaks. However, poor ionic conductivity and uncontrollable lithium dendrite growth have greatly limited the rapid development of polymer electrolytes. Hence, we report a composite polymer electrolyte combining a polyacrylonitrile (PAN) electrospun fiber membrane, flexible polydimethylsiloxane (PDMS) macromolecules and a polyethylene oxide (PEO) polymer. The introduction of PDMS with a highly flexible molecular chain, ultra-low glass transition energy and high free volume can help optimize lithium ion migration paths and improve the interface compatibility between the electrolyte and the electrode. In addition, the nano-network structure of the PAN nanofiber membrane can promote the interaction between adjacent polymer molecular chains and improve the mechanical properties of the composite electrolyte to suppress the lithium dendrite growth. The synergistic effect of the PDMS and PAN electrospun nanofiber membranes endows the composite electrolyte with superior ionic conductivity and excellent electrochemical stability towards lithium metal. The interface impedance of the Li/Li symmetric battery with the composite electrolyte after 15 days of continuous standing has no significant change compared with the initial state, and the battery can maintain stable cycling for 1200 h without short circuit under a dynamic current of 0.3 mA cm −2 . The obtained composite polymer electrolyte has potential application prospects in the field of high-energy lithium metal batteries.